Expression and purification of biologically active recombinant rabbit monocyte chemoattractant protein1 in Escherichia coli. Issue 9 (27th March 2018) - Boshtam, Maryam; Khanahmad Shahreza, Hossein; Feizollahzadeh, Sadegh; Rahimmanesh, Ilnaz; Asgary, Sedigheh
Abstract: Monocyte chemoattractant protein 1 (MCP1) with recruiting monocytes is an important factor at the beginning of inflammatory disorders such as atherosclerosis which seems its blocking preclude this process and help improvement of related diseases. To perform clinical research in this field, MCP1 protein is required but firstly, animal studies should be done. As the rabbit is a suitable model for many inflammatory disorders, and Escherichia coli BL21(DE3) (BL21) cell is a high-efficiency host for protein expression, we decided to produce recombinant rabbit MCP1 (rRMCP1) in BL21/pET28a system. After codon usage, a construct containing RMCP1 sequence was synthesized, cloned into the pET28a plasmid, and overexpressed in BL21 cells. Followed that, with changing expression condition such as cell concentration before the induction, time period, temperature, shaking rate and inducer concentration (IPTG), rRMCP1 expression was optimized, and purified by Ni-NTA. The biological activity of the expressed protein was verified using monocyte migration assay. Using this expression system, nearly 28 mg/mL rRMCP1 was produced at 26°C/180 rpm for 24 h in LB broth medium with 1 mM IPTG. Therefore, we were succeeded to express the intermediate level of rRMCP1 with this method. This amount of protein is sufficient for biological researches in the laboratory. Abstract : A recombinant RMCP1 was constructed and analyzed in an optimized Escherichia coli system.